GamiCSM: Relating education, culture and gamification - a link between worlds - Toda, Armando Maciel; Klock, Ana Carolina Tomé; Palomino, Paula Toledo; Rodrigues, Luiz; Oliveira, Wilk; Stewart, Craig; Gasparini, Isabela; Cristea, Alexandra Ioana; Isotani, Seiji (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The potential of gamification to improve users’ motivation and engagement influenced many researchers and professionals to analyse its effects in educational settings. While some studies focus on adapting game elements according to demographic and behavioural information of the user profile, few of them explore (or even consider) cultural factors. These cultural factors play an essential role in our societies’ development. Thus, this work proposes and evaluates a representative model to understand better the relationship between cultural factors and gamification within educational domains, namely the Gamification for Cultural Studies Model (GamiCSM). Through a qualitative approach, we map Hofstede’s cultural dimensions (i.e., power distance, individualism/collectivism, uncertainty avoidance, masculinity/femininity, long/short-term orientation, and indulgence/restraint) with a Taxonomy of Gamification Elements for Education (TGEEE), a recent model for gamification elements for educational environments. Furthermore, we adapted a survey to evaluate the resultant model with eight domain experts in gamification and education. Based on this evaluation, we are able to propose a starting model, containing some additional refinements and improvements. Thus, the main contributions of this work are: (i) the first model to relate game elements and cultural dimensions within educational domains and (ii) a state-of-the-art empirical study intersecting culture, gamification and education.